PENGARUH BAKTERI PROBIOTIK (Lactobacillus plantarum) PADA PAKAN UNTUK PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Dewi Sartika; Nurliah; Bagus Dwi Hari Setyono (Journal of Fish Nutrition, 2022)
This study aims to determine the effect of the probiotic bacteria Lactobacillus plantarum on the growth of tilapia. This research was conducted using an experimental method using Completely Randomized (CRD) with 5 treatments and 3 replications. The treatment given was the administration of probiotic bacteria L. plantarum from different dilutions of 30% of the amount of feed mixed into tilapia feed. The feed used is commercial pellet feed. The treatments are treatment 1 (P1): Administration of probiotic bacteria from a dilution of 10-3, treatment 2 (P2): Administration of probiotic bacteria from a dilution of 10-6, treatment 3 (P3): Administration of probiotic bacteria from a dilution of 10-9, treatment 4 (P4): Administration of probiotic bacteria from a dilution of 10-12, and treatment (P0): without administration of probiotics. Based on the results of research that has been carried out for 45 days, it can be said that treatment 3 (P3): Provision of probiotic bacteria at a dilution of 10-9 gave a significant effect on the growth of tilapia weight, feed conversion ratio, feed efficiency, and digestibility of tilapia feed. However, it did not have a significant effect on the increase in length and life of tilapia.